THE EXAMINATION OF THE CONCEPT OF MASCULINITY-FEMININITY IN THE CONTEXT OF QIRA'AT - Saylan, Nesrişah (Dinbilimleri Akad Arastirma Merkezi, 2026)
The qira'at's are related to the wording of the Qur'an and therefore, are connected to the Arabic language. In this context, linguistics and grammatical issues are at the center of the differences in qira'at. One aspect of these rules is the concept of masculinity and femininity, which is among the perspectives of qira'at differences. The existence of words described as feminine despite lacking feminine markers, the use of certain words in both masculine and feminine forms through semantic extension, the presence of a gap between the verb and its subject, and the issues related to plural words are some of the reasons for disagreements regarding masculine or feminine readings. Such differences are found across authentic, shadh, and all other types of recitation. In this study, the phenomenon of masculinity and femininity has been examined in the context of Qur'anic recitation. One of the objectives of this study is to identify these issues in qira'at and tafsir sources and to conduct a comparative analysis of opinions on the subject. Through this approach, the study aims to demonstrate that the differences in masculine or feminine readings do not contain any inconsistencies, contribute to a deeper understanding of the Qur'an, and provide a unique perspective by enriching the meaning of the Qur'an's interpretation.
Keywords: Recitation; Seven Recitations; Arabic Language; Masculine; Feminine